KEBERADAAN AMFIBI ORDO ANURA DI BLOK GUNUNG PUTRI TAMAN NASIONAL GUNUNG CIREMAI - Elditama Rezky; Iing Nasihin; Yayan Hendrayana; Toto Supartono; Ilham Adhya (Wanaraksa, 2022)
The research seeks to determine the habitat conditions, characteristics, and diversity of amphibians of the order Anura. The method used in this research is a combination of Line Transect and Visual Encounter Survey (VES). Based on observations using a combination of the Line Transect method and the Visual Encounter Survey method, the number of amphibians species found was 8 species from 5 families including 1 type of family Bufonidae, 2 types of family Dicroglossidae, 1 type of family Megophrydae, 2 types of family Ranidae, and 2 species of family Rhacophoridae. The index of amphibian species diversity in the mount Putri river flow of Mount Ciremai National Park (H') which was obtained at the research location of the Mount Putri Ciinjuk river flow was 1.60. The value of the Eveness index of amphibians that obtained in the Mount Putri river flow was E = 0.77 and The value of the wealth index obtained is R = 1.48 then the temperature and humidity ranges from 19.3 – 20.0°C and 90.5% – 98.4%, with water pH value 6 – 7. The flow of the Mount Putri Ciinjuk river is a balanced habitat for amphibian life where the flow is formed from two steep Mount Ciremai slopes with moist litter conditions and dense canopy cover.Penelitian ini bertujuan untuk mengetahui kondisi habitat, karakteristik, dan keanekaragaman amfibi ordo Anura. Metode yang digunakan dalam penelitian ini adalah kombinasi Line Transect dan Visual Encounter Survey (VES). Berdasarkan pengamatan menggunakan kombinasi metode Line Transect dan metode Visual Encounter Survey, jumlah jenis amfibi yang ditemukan adalah 8 jenis dari 5 famili diantaranya 1 jenis famili Bufonidae, 2 jenis famili Dicroglossidae, 1 jenis famili Megophrydae, 2 jenis famili Ranidae, dan 2 jenis famili Rhacophoridae. Indeks keanekaragaman jenis amfibi di aliran sungai Gunung Putri Taman Nasional Gunung Ciremai (H') yang diperoleh di lokasi penelitian aliran sungai Gunung Putri Ciinjuk adalah sebesar 1,60. Nilai indeks kemerataan amfibi yang diperoleh di aliran sungai Gunung Putri adalah E = 0,77 dan Nilai indeks kekayaan yang diperoleh adalah R = 1,48 kemudian suhu dan kelembaban berkisar antara 19,3 – 20,0°C dan 90,5% – 98,4% , dengan nilai pH air 6 – 7. Aliran sungai Gunung Putri Ciinjuk merupakan habitat yang seimbang bagi kehidupan amfibi dimana aliran tersebut terbentuk dari dua lereng Gunung Ciremai yang terjal dengan kondisi serasah yang lembab dan tutupan tajuk yang rapat.